Performance of Leguminous Tree Species in Sand-mined Soil Under Nursery Conditions - Olajuyigbe, Samuel; Sijuola, Temilola (Indian Forester, 2022)
Early growth performance of Delonix regia, Albizia lebbeck, Albizia saman and Leuceana leucocephala in soil from an abandoned sand mining site was investigated. Using a completely randomized block design, forty seedlings from each species were transplanted into topsoil and sand-mined soil. Total height, collar diameter, and number of leaves were monitored fortnightly, for 16 weeks. Biomass accumulated by the seedlings was determined, while root nodulation and foliar chlorophyll content were assessed. Significant differences were observed in the main and interaction effects of soil type and species type on growth variables, with higher growth in topsoil. Delonix regia in topsoil had the highest total height (41.01±3.14 cm) and collar diameter (7.11±0.34 cm), while A. lebbeck had the highest number of leaves (11.39±0.37). Biomass accumulation followed the trend: D. regia>A. lebbeck> A. saman>L. leucocephala for both topsoil and sand-mined soil treatments. Highest nodulation was in A. saman (13) growing in sand-mined soil while D. regia (6.20±1.20 mg/g) in topsoil had the highest chlorophyll content. All the species survived in the sand-mined soil with D. regia and A. lebbeck out performing the other species, indicating their potential choice for rehabilitation of sand mining quarries.